2015
DOI: 10.1586/14760584.2015.1078240
|View full text |Cite
|
Sign up to set email alerts
|

An update on barriers to adolescent human papillomavirus vaccination in the USA

Abstract: Human papillomavirus is the most common sexually transmitted infection in the USA. It is the primary cause of almost all cervical cancers as well as several other cancers that affect both men and women. Adolescents of both genders can now prevent transmission of the most common oncogenic strains of human papillomavirus by obtaining a safe, three-dose vaccine series. However, despite its potential to save lives and reduce severe morbidity, many US adolescents have not been vaccinated. This is in contrast to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 70 publications
(40 reference statements)
1
18
0
7
Order By: Relevance
“…Other barriers, especially early after the vaccine's introduction, included: cost to both patients and providers, parents' lack of awareness, and missed opportunities for vaccination. [72][73][74] Some of these barriers were likely caused directly or indirectly by lack of state mandate, rapidly changing guidelines, gender-based guidelines, and poor tracking of HPV vaccination.…”
Section: Hpv Vaccination Disparitiesmentioning
confidence: 99%
“…Other barriers, especially early after the vaccine's introduction, included: cost to both patients and providers, parents' lack of awareness, and missed opportunities for vaccination. [72][73][74] Some of these barriers were likely caused directly or indirectly by lack of state mandate, rapidly changing guidelines, gender-based guidelines, and poor tracking of HPV vaccination.…”
Section: Hpv Vaccination Disparitiesmentioning
confidence: 99%
“…HPV vaccines were considered to prevent some sexually transmitted diseases by adolescents in the United States. 43 Young adults might be reluctant to receive the HPV vaccine because they were afraid of being labeled sexually active. 28 At the same time, Jumaan et al found that focusing messages on cervical cancer protection rather than sexually transmitted diseases prevention appeared to help minimize sensitivities around girls' sexuality.…”
Section: Influential Factors For Acceptance Of Hpv Vaccinationmentioning
confidence: 99%
“…Patel et al, 2016 (16) (20) Identificar barreras a la vacunación contra el VPH en adolescentes en EE.UU.…”
Section: Estudio Piloto / Cuestionario Transversalunclassified
“…La mayoría de los adolescentes tienen un nivel deficitario de conocimiento sobre el VPH, independientemente del género (2,7,(10)(11)(12)(13)(16)(17)(18)20,22,(25)(26)(27)(28) . Los estudios informan el bajo nivel de conocimiento sobre el virus en diversas partes del mundo, siendo realizados nacional e internacionalmente, ocurriendo no sólo en instituciones de enseñanza, como también en la comunidad y clínicas de salud tales como: en escuelas de México (2,11) , del municipio de Crato, en Ceará (7) , del territorio urbano y rural de Grecia (10) , de Uganda (25) , Universidad de Turquía (18,22) , escuelas y universidades de Marruecos (26) , así como en la población de Estados Unidos (12,20) , de Europa (16) , de Indonesia (17) y del Reino Unido (28) y clínicas de salud de Haití (13) .…”
Section: Nivel De Conocimiento Y Variable De Conocimientounclassified